Characteristics of Fe-yttria composites fabricated by powder metallurgy method - Marina, Marzuki; Kartini, Alir; Wan Abdul Rahman Assyahid, Wan Ibrahim; Nooraizedfiza, Zainon; Mohd Asri, Selamat; Mohd Zamzuri, Mohammad Zain (Trans Tech Publications, 2013)
Link to publisher's homepage at http://www.ttp.net/